Scene construction impairments in frontotemporal dementia: Evidence for a primary hippocampal contribution. (3rd February 2020) - Wilson, Nikki-Anne; Ramanan, Siddharth; Roquet, Daniel; Goldberg, Zoë-Lee; Hodges, John R.; Piguet, Olivier; Irish, Muireann
Abstract: The capacity to generate naturalistic three-dimensional and spatially coherent representations of the world, i.e., scene construction, is posited to lie at the heart of a wide range of complex cognitive endeavours. Clinical populations with selective damage to key nodes of a putative scene construction network of the brain have provided important insights regarding the contribution of medial temporal and prefrontal regions in this regard. Here, we explored the capacity for atemporal scene construction, and its associated neural substrates, in the behavioural-variant of frontotemporal dementia (bvFTD); a neurodegenerative brain disorder in which atrophy systematically erodes medial and lateral prefrontal cortices with variable medial temporal lobe involvement. Nineteen bvFTD patients were compared to 18 typical Alzheimer's Disease (AD), and 25 healthy older Control participants on a scene construction task. Relative to Controls, both patient groups displayed marked impairments in generating contextually detailed and spatially coherent scenes, with bvFTD indistinguishable from AD patients across the majority of task metrics. Voxel-based morphometry, based on structural brain MRI, revealed divergent neural substrates of scene construction performance in each patient group. Despite widespread medial and lateral prefrontal atrophy, the capacity to generate richly detailed and spatially coherent scenes in bvFTD was found to rely predominantly upon the integrity of right medial temporal structures, including the hippocampus and parahippocampal gyrus. Scene construction impairments in AD, by contrast, hinged upon the integrity of posterior parietal brain regions. Our findings in bvFTD resonate with a large body of work implicating the right hippocampus in the construction of spatially integrated scene imagery. How these impairments relate to changes in autobiographical memory and prospection in bvFTD will be an important question for future studies to address. Highlights: The capacity to construct spatially integrated scene imagery was assessed in bvFTD. Patients displayed marked deficits in generating richly detailed and spatially coherent scenes. Neural correlates of scene construction performance were established using VBM. Right anterior hippocampal atrophy underpinned scene construction deficits in bvFTD. Our findings confirm the centrality of the hippocampus for constructive endeavours.